THE INFLUENCE OF BRAND AMBASSADOR, PRODUCT QUALITY, AND PRICE ON PURCHASING DECISIONS FOR COLLAGENA - Ardiprawiro (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of brand ambassadors, product quality, and price on consumers’ purchase decisions regarding Collagena, a collagen supplement. Against the backdrop of a rapidly expanding health and beauty market, the research investigates how endorsements by public figures, perceptions of product efficacy, and pricing strategies shape purchasing behavior. A quantitative survey was conducted using a structured questionnaire distributed online, yielding 100 valid responses from individuals who had purchased or considered purchasing Collagena. The measurement items for Brand Ambassador, Product Quality, Price, and Purchase Decision were validated (all item–total correlations r > 0.197) and demonstrated strong reliability (Cronbach’s α = 0.884). Classical assumption tests confirmed normality (Kolmogorov–Smirnov p = 0.200), no multicollinearity (VIF < 10 for all variables), and homoskedasticity (Glejser’s test p > 0.05). Multiple linear regression analysis revealed that Brand Ambassador (β = 0.270, p = 0.001), Product Quality (β = 0.319, p < 0.001), and Price (β = 0.335, p < 0.001) each exert a significant positive partial effect on purchase decisions. Simultaneously, these three factors collectively explained 39.5% of the variance in purchase decision (Adjusted R² = 0.395, F = 22.578, p < 0.001). The findings suggest that Collagena’s marketing strategies should prioritize credible ambassador partnerships, transparent quality communication, and value-based pricing to strengthen consumer trust and drive sales. Future research may explore additional variables—such as brand image or promotional activities—to account for the remaining variation in purchase behavior.